Contamination of Surface Water with Veterinary Antibiotics in Tiaoxi River Basin, East China - Jiang1, Jinping; Ye1, Lili; Chen2, Yongshan (Asian Journal of Chemistry, 2014)
The assessment of veterinary antibiotics pollution in drinking water sources is a critical issue for potential threat for human health. The occurrence and distribution of 14 selected antibiotics representing five categories (tetracyclines, sulfonamides, fluoroquinolones, macrolides and chloramphenicols) were investigated in surface waters and swine wastewater from Tiaoxi river basin using HPLC/MS/MS. The results indicated that contamination levels of the individual antibiotics in surface waters were significantly different. Tetracyclines (including tetracycline, oxytetracycline, chlortetracycline and doxycycline) and sulfonamides (including sulfadiazine, sulfamethoxazole and sulfamethazine) were the dominant antibiotics present in aqueous samples along Tiaoxi river but their concentrations varied greatly with timing and locations of sampling. The higher antibiotics concentrations were found in fishing ponds and soft-shell turtle pond than the samplings of Tiaoxi river and drinking water source, but swine wastewater with the highest antibiotics concentrations in all sampling sites. Agricultural activities (e.g., swine or soft-shell turtle feeding) may be major sources of contaminants in the aqueous environment. So control measures must be done to limit antibiotics abuse in livestock farming and aquaculture and to avoid swine wastewater poured into rivers for cleaning drinking water sources and ecological health.